“Russian Idea” in Bulgarian Social and Political Life of Last Quarter of 19th Century (by Example of Views and Activities of the Highest Church Hierarchs) - V. V. Bondareva (Научный диалог)
The article is devoted to the main issues of expression of the “Russian idea” in the social and political life of Bulgarians in the last quarter of the 19th century. The relevance of the study is determined by the increased interest in the spread of Russian influence in the modern world and, in particular, within the South-Eastern Europe, which in the 20th century was the sphere of influence of the USSR. The author analyzes the historical significance, the scope and content of the “Russian idea” in the life of the Bulgarian society and state on the example of the attitudes and activities of the Supreme Church hierarchs (Exarch Joseph I and the Metropolitan Bishop Clement of Tarnovo). “Russian idea” is considered in the work not just as a structural element of a certain system of socio-political views, but also as a way of organizing the historical and political space of Bulgaria, as a special principle in the strategic modeling of the direction of its historical development with a certain geopolitical perspective on the basis of Slavs and Orthodoxy. It is concluded that the “Russian idea” in the last quarter of the 19th - early 20th centuries was a key element of the socio-political life of Bulgaria, the most important historical characteristic of its socio-cultural space and national consciousness. However, despite this, the “Russian idea” could not become a political choice of the Bulgarian state, as in the early 20th century in the political space of Bulgaria prevailed anti-Russianism, supported by a narrow group of the ruling elite.